KAJIAN TEORITIS STRATEGI EFEKTIF PENURUNAN KEMATIAN BAYI - Rokhmawan, Ulum Rokhmat; Yuly Peristiowati; Dwi Helynarti Syurandhari (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Infant mortality rate is one of the important indicators of public health. Efforts to reduce infant mortality have been made by the government from year to year. So the assessment of the effectiveness of these activities is interesting to explore. The method used to write this article is a systematic review, which is limited to searching the literature for the last 5 years (2018-2023). Search results for articles that match the keyword obtained 126 articles. However, after further searching, 8 articles were obtained that fit the inclusion criteria and themes to be discussed. The results of the study explain that not all programs are running well. So that coordinative efforts between various sectors are needed in order to achieve the IMR reduction target as planned. Efforts have not been implemented optimally, the effectiveness of programs implemented across programs and across sectors is able to reduce infant mortality in Indonesia little by little. Local governments are expected to make coordinated efforts involving all service sectors and community organizations to participate in the success of the program and improve the achievement of the work program that has been planned every year.